Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja pada Pegawai Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Binjai - Dian Sari Pindawati; Khamo Waruwu; Mella Yunita (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The purpose of this study is to determine the influence of organizational culture and leadership style on the performance of employees of the Regional Development Planning Agency (Bappeda) of Binjai City. This study was conducted on employees of the Regional Development Planning Agency (Bappeda) of Binjai City with a population and sample of 60 employees. The research instrument was a questionnaire with a Likert scale model. The requirements test was carried out to test normality. The data analysis technique used was the Multiple Regression technique at a significance level of a = 0.05. The results of this study indicate that organizational culture (X1) has a partial and significant effect on performance at the Bappeda of Binjai City, where the calculated t is greater than the t table (1.742 ˃ 1.67203) with a significant value of 0.007. Meanwhile, leadership style (X2) has a partial and significant effect on the performance of Bappeda Kota Binjai employees with a calculated t value greater than the t table (5.166 ˃ 1.67203) with a significant value of 0.000. Based on the SPSS output, it is known that the value of R squared is 0.421, meaning that the variance of employee performance variables can be explained by organizational culture and leadership style variables by 42.1 percent, while the remaining 57.9 percent is explained by other variables not included in this model, in other words there are still other independent variables that affect performance.